Investigating the Mechanism of Live Streaming on Purchase Decisions: The Mediating Role of Trust - Angelina Rumondor, Vina; Bachri, Syamsul; Sutomo, Maskuri; Mandala Putra, Setiawan (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of live streaming on purchase decisions, with consumer trust as a mediating variable, in TikTok Shop purchases of Glad2Glow skincare products. The objective was to analyze the direct effect of live streaming on consumer trust and purchase decisions, as well as the mediating role of consumer trust. This quantitative study involved 75 respondents and used Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results showed that live streaming significantly affected consumer trust and purchase decisions, while consumer trust also significantly influenced purchase decisions and mediated the relationship. These findings imply that effective live streaming can strengthen trust and encourage purchasing behavior. Keywords: Live Streaming, Purchase Decision, Consumer Trust, Tiktok Shop, Skincare, Glad2Glow